IMMUNOSTIMULATORY EFFECT OF METHANOL EXTRACT OF FLAMBOYANT LEAF [Delonix regia (Boj. ex Hook.) Raf.] IN MICE - Kartini Eriani; Ainsyah Ainsyah; Rosnizar Rosnizar; Yunita Yunita; Ichsan Ichsan; Al Azhar (Universitas Syiah Kuala, 2018)
Abstract. Flamboyant [Delonix regia (Boj. ex Hook) Raf.] leaf contains flavonoid compounds that are expected to have immunostimulatory effect. This research was done to determine the effect of flamboyant leaf extract on immune response by accessing the activity of immune cells and capability test the extract as immunostimulant in mice. Leaf extraction was done by maceration using methanol in the Laboratory of Biology of Chemistry Department, Faculty of Mathematics and Natural Sciences of Syiah Kuala University whereas animal treatment and testing were carried out Micro-technique Laboratory of Biology Department of the same faculty. This research used 20 male mice strain Swiss-Webster aged 7-8 weeks were randomly assigned to 4 treatment groups with five replications each. Group 1 (P0) was untreated control; group 1-3 were mice administration flamboyant leaf extract 250 mg/kg BW (P1), 500 mg/kg BW (P2), and 750 mg/kg BW (P3) per oral. The treatments were given for 14 days after one week of adaptation period. Blood samples were collected before and after extract treatment and used for leukocyte count analysis. Phagocytosis activity was accessed by carbon clearance assay on day 15. At the end of the study, all mice were sacrificed for spleen weight analysis. Data obtained was analyzed by Analysis of Variance followed by Tukey test (Leukocyte count and spleen weight) or regression analysis (carbon clearance). The results showed a flamboyant leaf extract administration resulted in increased leukocyte counts that were significantly different (p0.05) between treatment groups. Phagocytosis test indicated the extract had moderate to strong immunostimulatory effect whereas spleen weight analysis did not show any difference among treatment groups. In conclusion, flamboyant leaf methanol extract was able to increase immune cells and had potential immunostimulatory activity in mice.Keywords: Delonix regia, immunostimulant, leukocytes, lymphocyte proliferation.